Teori-Teori dalam Psikologi Pendidikan dan Implikasinya dalam Pendidikan Islam - Rohmah, Mar-Atin Nabila; Rohimah, Siti (TSAQOFAH, 2026)
Educational psychology plays an important role in understanding students’ learning processes and designing effective instruction, so that learning theories become a conceptual foundation for educators in determining appropriate approaches, strategies, and methods. This article aimed to examine the main learning theories in educational psychology—namely behaviorist, cognitive, humanistic, and constructivist theories—and to analyze their implications in the context of Islamic education. A library research method was employed by reviewing various relevant books and journal articles. The findings show that each learning theory has distinct characteristics, basic assumptions, and pedagogical applications: behaviorist theory emphasizes behavior reinforcement through stimulus–response mechanisms, cognitive theory focuses on internal mental processes, humanistic theory is oriented toward the development of potential and the wholeness of the self, while constructivist theory positions learners as active subjects in constructing knowledge. Nonetheless, these four theories can complement one another when integrated with Islamic values, so that the learning process becomes not only academically effective but also oriented toward character formation, the strengthening of spirituality, and the personality balance of learners. Thus, the integration of learning theories within the framework of Islamic education constitutes an essential foundation for developing holistic and character-based instructional practices.